Diagnosis and treatment of acute pulmonary embolism during pregnancy - Gleiny Vázquez Hernández; Roman Vasallo Peraza; Yoarlen Toledo Poey (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Acute pulmonary embolism is one of the most frequent causes of mortality and serious morbidity during pregnancy; however, there is no consensus on its definitive diagnosis. Objective: To expose the most important considerations for the diagnosis and treatment of pregnant women with suspected pulmonary embolism. Material and Methods: Literature review on the subject, published from 2012 to the present, which included the PubMed/MEDLINE, EMBASE, Lilacs and SciELO databases. Development: The current guidelines show controversies in relation to the use of risk prediction rules, the quantification of D-dimer and the indication of imaging studies. Clinical evaluation continues to be the main diagnostic substrate, but it has been pointed out that both a normal ventilation-perfusion scintigraphy and a negative CT angiography accurately exclude pulmonary embolism during pregnancy. The use of heparins is the treatment of choice, while the new oral anticoagulants are not recommended in pregnancy due to the lack of studies that support their safety. Fibrinolysis can be considered in high-risk pregnant women (severe hypotension, shock, or cardiorespiratory arrest). Conclusions: The management of these patients should be undertaken by a multidisciplinary team, which will allow better maternal and perinatal results.